Iatrogenic Delayed Aortic Injury Following a Surgical Stabilization of Flail Chest - Junepill Seok; Hyun Min Cho; Seon Hee Kim; Ho Hyun Kim (Journal of Trauma and Injury)
Most of aortic injuries after blunt chest trauma usually occur at the aortic isthmus and are identified in the emergency department soon after arrival. Delayed aortic injures by fractured posterior ribs, however, are relatively rare and have been reported only a few times. We recently experienced an iatrogenic descending aortic injury sustained as a result of a direct puncture by a sharp rib end after surgical stabilization of rib fractures.